Data analysis of student profiles and dropout rates in the industrial engineering course at the federal University of Catalão - Coelho, Helena Alves; Rabelo, Sarah dos Santos; Pereira, Victorya Silva; Santos, Aline Gonçalves dos; Araújo, Fernando de; Fonseca Júnior, Lázaro Antônio da (Brazilian Journal of Production Engineering, 2024)
Industrial Engineering encompasses a broad education, allowing its professionals to have generalist knowledge to work in different areas. One of the main challenges faced by programs in this field is the high dropout rate among students. Therefore, it is important that data is analyzed in a way that provides effective management of these courses. In this context, the present work was developed with the aim of providing a data analysis of the Industrial Engineering program at the Federal University of Catalão to assist in its planning and decision-making. To achieve this, quantitative research was conducted, with data collected from students who enrolled between the years 2008 and 2022. This data was organized using Excel and processed using Power BI. The results show that the largest number of entrants in the analyzed program comes from the region where the university is located, that there is a higher number of male entrants, and that there was a significant increase in student dropout rates in 2022, a post-pandemic period due to COVID-19.
Keywords: Production Engineering; Students; Incoming Students